Features of lipid-lowering therapy in liver transplant recipients - A. A. Kucherov; A. I. Ershova; V. E. Syutkin; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Liver transplantation (LT) requires not only a carefully organized system for monitoring the condition of patients in the early postoperative period, but also reliable coordination of the actions of doctors of different specialties in the long-term period. This is due to improved survival of liver transplant recipients and a shift in the mortality structure towards cardiovascular diseases and the need to correct metabolic complications that often occur in recipients, in particular hyperlipidemia. Treatment of lipid metabolism disorders after LT includes lifestyle changes, immunosuppressive and lipid-lowering therapy (LLT), which reduces cardiovascular risk. The use of LLT in patients after LT is limited by potential side effects caused by drug interactions, in particular myopathy up to rhabdomyolysis. According to current clinical guidelines, the safest treatment for patients after LT is pravastatin and fluvastatin, the use of which is limited by low availability and low efficacy. It seems promisingto improve LLT in patients after LT through the use of ezetimibe, which has a potentially favorable tolerability profile when combined with immunosuppressants, as well as pitavastatin, which is metabolized through cytochrome P-450 isoenzymes not involved in the metabolism of immunosuppressants, and metabolically neutral PCSK9 inhibitors.